Single market for the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
The Caribbean Community (CARICOM) has become the world s newest trade bloc, with the launch of the CARICOM Single Market (CSM)..